Calculation of energy release function of focused ion beam in solids; Методология проектирования молодежного научно-инновационного пространства как основа подготовки современного инженера - Ryabkina X. S. (Integrity of traditions and innovations as the basis for the development of modern engineering science, 2014)
Заглавие с экрана